Compatible solute addition to biological systems treating waste/wastewater to counteract osmotic and other environmental stresses: a review - Vyrides, Ioannis; Stuckey, David (My University, 2017)
This study reviews the addition of compatible solutes to biological systems as a strategy to counteract osmolarity and other environmental stresses. At high osmolarity many microorganisms accumulate organic solutes called “compatible solutes” in order to balance osmotic pressure between the cytoplasm and the environment. These organic compounds are called compatible solutes because they can function inside the cell without the need for special adaptation of the intracellular enzymes, and also serve as protein stabilizers in the presence of high ionic strength. Moreover, the compatible solutes strategy is regularly being employed by the cell, not only under osmotic stress at high salinity, but also under other extreme environmental conditions such as low temperature, freezing, heat, starvation, dryness, recalcitrant compounds and solvent stresses. The accumulation of these solutes from the environment has energetically a lower cost than de novo synthesis. Based on this cell mechanism several studies in the field of environmental biotechnology (most of them on biological wastewater treatment) employed this strategy by exogenously adding compatible solutes to the wastewater or medium in order to alleviate environmental stress. This current paper critically reviews and evaluates these studies, and examines the future potential of this approach. In addition to this, a strategy for the successful implementation of compatible solutes in biological systems is proposed.
Keywords: Biological systems; Compatible solutes; Environmental stresses; Osmolarity; Wastewater